Xenogenous collagen matrix and/or enamel matrix derivative for treatment of localized Gingival recessions: A randomized clinical trial. Part II: Patient-reported outcomes - Dos Santos, Manuela Rocha; Sangiorgio, João Paulo Menck; Da Silva Neves, Felipe Lucas; França-Grohmann, Isabela Lima; Nociti, Francisco Humberto; Ruiz, Karina Gonzales Silverio; Santamaria, Mauro Pedrine; Sallum, Enilson Antonio (Wiley, 2017)
Background: Gingival recession (GR) might be associated with patient discomfort due to cervical dentin hypersensitivity (CDH) and esthetic dissatisfaction. The aim is to evaluate the effect of root coverage procedure with a xenogenous collagen matrix (CM) and/or enamel matrix derivative (EMD) in combination with a coronally advanced flap (CAF) on CDH, esthetics, and oral health-related quality of life (OHRQoL) of patients with GR. Methods: Sixty-eight participants with single Miller Class I/II GRs were treated with CAF (n = 17), CAF + CM (n = 17), CAF + EMD (n = 17), and CAF + CM + EMD (n = 17). CDH was assessed by evaporative stimuli using a visual analog scale (VAS) and a Schiff scale. Esthetics outcome was assessed with VAS and the Questionnaire of Oral Esthetic Satisfaction. Oral Health Impact Profile-14 (OHIP-14) questionnaire was used to assess OHRQoL. All parameters were evaluated at baseline and after 6 months. Results: Intragroup analysis showed statistically significant reduction in CDH and esthetic dissatisfaction with no intergroup significant differences (P >0.05). The impact of oral health on QoL after 6 months was significant for CAF + CM, CAF + EMD, and CAF + CM + EMD (P <0.05). Total OHIP-14 score and psychologic discomfort, psychologic disability, social disability, and handicap dimensions showed negative correlation with esthetics. OHIP-14 physical pain dimension had positive correlation with CDH (P <0.05). OHIP-14 showed no correlation with percentage of root coverage, keratinized tissue width, or keratinized tissue thickness (P >0.05). Conclusion: Root coverage procedures improve patient OHRQoL by impacting on a wide range of dimensions, perceived after reduction of CDH and esthetic dissatisfaction of patients with GRs treated with CAF + CM, CAF + EMD, and CAF + CM + EMD.
Keywords: Dentin sensitivity; Esthetics, dental; Gingival recession; Quality of life; Surgery, oral